Comparison of gastric volumes using ultrasound in term pregnant women with and without gestational diabetes before elective cesarean delivery: an observational cohort study - Feyza Çalışır; Gözen Öksüz (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective This study aimed to evaluate the impact of gestational diabetes mellitus (GDM) on gastric volume and content using gastric ultrasonography in term pregnant women undergoing elective cesarean delivery. Given the increased aspiration risk in pregnant patients due to physiological changes, GDM-related gastric motility alterations may further complicate anesthetic management.Methods A prospective observational cohort study included 60 pregnant women scheduled for elective cesarean delivery: 30 diagnosed with GDM and 30 without GDM. Gastric ultrasonography was performed in both the supine and right lateral decubitus positions to assess antral cross-sectional area (CSA), gastric volume, and content classification (Grade 0, 1, or 2). Quantitative measurements, fasting durations, demographic information, and preoperative blood glucose levels were collected and statistically analyzed.Results No significant differences were observed in gastric volumes between the GDM group (86.14 ± 38.43 ml) and the control group (77.89 ± 44.54 ml; p = 0.49). However, Grade 1 and Grade 2 gastric contents were significantly more prevalent in the GDM group (56.7% Grade 1, 16.7% Grade 2) compared to the control group (16.7% Grade 1, 0% Grade 2; p < 0.001). Preoperative blood glucose levels were significantly higher in the GDM group.Conclusions Gastric ultrasonography is a valuable, noninvasive method for evaluating gastric content and volume in pregnant women, particularly those with GDM. The higher prevalence of residual gastric content in GDM patients indicates a potential delay in gastric emptying, which could increase perioperative aspiration risk despite adherence to standard fasting protocols. These findings highlight the need for individualized anesthetic strategies, particularly in emergency and high-risk obstetric anesthesia settings.